1993
DOI: 10.3109/00365529309103132
|View full text |Cite
|
Sign up to set email alerts
|

Biotinidase Activity in Patients with Liver Disease

Abstract: To investigate whether biotinidase deficiency may occur in liver disease, we determined biotinidase activity, biotin levels, and organic acids in patients with liver disease. Serum biotinidase activity in patients with liver disease (2.63 +/- 1.40 nmol/min/ml) was significantly lower than in the control group (5.43 +/- 1.06 nmol/min/ml). Serum biotinidase activity in decompensated liver cirrhosis (LC) and hepatoma was significantly lower than in acute viral hepatitis (AVH), chronic viral hepatitis (CVH), and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 12 publications
1
8
0
1
Order By: Relevance
“…Hyperammonemia, which was detected in groups B and C, is reported among patients receiving VPA therapy (4). Lower concentrations of serum albumin were also found in our patients, as Nagamine et al (9) reported in patients with liver disease, who also had low biotinidase activity. Furthermore, the decreased biotinidase activities (Table 1) found in our patients were not related to the severity of their skin side effects of VPA, even though the number of patients who exhibited additional problems other than alopecia, seborrheic skin rash, and pruritus was small.…”
Section: Discussionsupporting
confidence: 90%
“…Hyperammonemia, which was detected in groups B and C, is reported among patients receiving VPA therapy (4). Lower concentrations of serum albumin were also found in our patients, as Nagamine et al (9) reported in patients with liver disease, who also had low biotinidase activity. Furthermore, the decreased biotinidase activities (Table 1) found in our patients were not related to the severity of their skin side effects of VPA, even though the number of patients who exhibited additional problems other than alopecia, seborrheic skin rash, and pruritus was small.…”
Section: Discussionsupporting
confidence: 90%
“…A report by Nagamine et al showed that the mean biotinidase activity in the liver patients was significantly lower than in control group (9). Their data indicated that the decrease of biotinidase activity tended to parallel the degree of liver disease (9). Their data indicated that the decrease of biotinidase activity tended to parallel the degree of liver disease (9).…”
Section: Discussionmentioning
confidence: 94%
“…Nagamine et al 14 have shown that reduced serum biotinidase correlated with reduced serum albumin in patients with both acute and chronic liver diseases. They also showed reduced serum biotinidase correlated with reduced serum biotin and increased urinary biotin levels in patients with liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that biotinidase activities in the disease groups were sig- © 2007 The Japan Society of Hepatology nificantly lower than control values, even after adjusting for bilirubin levels in this fashion. Nagamine et al 14 have shown that reduced serum biotinidase correlated with reduced serum albumin in patients with both acute and chronic liver diseases. They also showed reduced serum biotinidase correlated with reduced serum biotin and increased urinary biotin levels in patients with liver disease.…”
Section: Discussionmentioning
confidence: 99%